The impact of talent attraction, talent development and talent retention on job satisfaction in hospitality industry - Chan, Jia Ying; Chai, Wen Xin; Koh, Chi Kuan; Ngo, Siang Li; Teh, Ling Li (2020)
This primary objective of this research is to study the impact of talent management on job satisfaction in hospitality industry in Malaysia. The study has been conducted is to identify the independent variables which talent attraction, talent development, and talent retention will impact the dependent variable which job satisfaction. The specific objective is to identify whether there is a significant relationship between talent attraction, talent development and talent retention toward the employees’ job satisfaction in this research. The primary data of this research was assembled by a researcher directly from first-hand such as questionnaires. 400 sets of questionnaires were distributed to employees who live in Northern region of Peninsular Malaysia such as Perak, Perlis, Kedah and Penang. After the questionnaires assembled, Cronbach’s alpha will be used for testing the data’s reliability in the relation between dependent variable and independent variables. Besides, Statistical Package for the Social Sciences (SPSS) software also be used to analyse the data. Pearson Correlation Coefficient is to test the association between variables. All variables are falling within the 0.70 – 0.89 which mean correlation between independent variables and dependent variable is strong. Furthermore, multiple regression is to evaluate two or more independent variables toward the dependent variable. It shows that there is significant relationship between talent management and job satisfaction. To sum up, based on the finding, the research indicated that talent management has positive significant relationship with employees’ job satisfaction in hospitality industry. This research also will further concern on implications of the study, limitations of the study and recommendations.